Penguatan pendidikan keluarga melalui penyuluhan kesehataan tentang pencegahan stunting - NUNUK NURHAYATI; Partina (STIKES dan AKZI Karya Husada Kediri, 2022)
The current national issue and the focus of the Indonesian government are stunting. Stunting is a condition where the child's body is shorter than the height of children his age. The prevalence of stunting in Indonesia in 2021 is 24.4%, which in 2018 reached 30.8%. According to SSGI, in 2021 the prevalence of stunting in Mojokerto Regency will increase by 27.4% even though data from SSGI in 2019 the prevalence is only 16.8%. Stunting is important to be handled and is the responsibility of all sectors including health academics because it involves the quality of human resources and children's vulnerability to disease and cognitive developmental barriers that affect the level of intelligence and productivity of children in the future. The methods used in community service today are in the form of health counseling and discussions in a warm atmosphere to strengthen family education, including the understanding of stunting and its characteristics, causes of stunting, the impact of stunting, how to prevent and overcome stunting and how to improve the quality of nutrition in families. . With this community service, it can help the Indonesian government in 2024 reduce the prevalence of stunting to reach 14%, which means it must reduce the prevalence by 10.4% in the next 2 years.